Digital Communication Strategy in Improving Image at PT. Sarana Mulya Logistik in Jakarta - Akbar, Ali; Furrie, Wulan; Utami, Suci; Venny Lestari; Kayo, Puti; Hananto, Tri (Formosa Journal of Sustainable Research, 2024)
In today's modern era, Digital Communication has become the most important thing in an organization or company. Besides being a demand, the digital communication function at PT. Sarana Mulya Logistik is very important to run in order to create an increase in the good image of the company and its digital communication. This research aims to find out the Digital Communication Strategy in Improving Image at PT. Sarana Mulya Logistik Jakarta along with its obstacles and solutions. This type of research uses qualitative research methods with a descriptive approach and data collection techniques in the form of observation, interviews, documentation, and literature study. The results of this study indicate that the Digital Communication Strategy in Improving Image at PT. Sarana Mulya Logistik Jakarta is to build a Networkable or strong network and convey the company's values and mission consistently to various digital platforms. PT. Sarana Mulya Logistik Jakarta in its digital communication strategy emphasizes having a deep understanding of the target audience and building messages that are relevant to the company's values and personality. Communication should be done through the right channels, be it through the company website, social media, email, or other channels that match the habits and preferences of the audience. A good and directed communication strategy is the key to improving the image of PT. Sarana Mulya Logistik Jakarta